Hubungan Komitmen Afektif dengan Kepuasan Kerja pada Guru SMK - Aan Hartati; Nilam Widyarini (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to determine the relationship between affective commitment and job satisfaction in vocational teachers. This study involved 59 vocational school teachers at one of the state vocational schools in Tangerang Regency, Banten Province. The research method used is quantitative by using a questionnaire as a research data collection tool. The data analysis technique used is using the SPSS version 26 program with the results of the study that there is a significant relationship between affective commitment and job satisfaction in vocational teachers. Keywords: affective commitment, job satisfaction, vocational teachers.